NARCISSISM IN PAULA HAWKINS' NOVEL THE GIRL ON THE TRAIN - Riska Rahayu Roisiah; Pramudana Ihsan; Wijayadi Wijayadi (Universitas Islam Sumatera Utara (UISU), 2021)
Narcissism is one of the most common diseases in psychology, but its concern is the least. Therefore, this research was focused on narcissism disorder of one of the main characters named Megan Hipwell in the novel The Girl on the Train by Paula Hawkin. The analysis was done by applying psychoanalytic theory, in narcissism, which is the most common mental disorder among the members of a society. The method of research was qualitative, which required an in-depth analysis of the literary works used by the writers of this research according to the selected theories. The analysis was aimed to find illustrations and evidence of the main character in the novel The Girl on the Train to illustrate narcissism disorder. In this research, it was found that the main character suffered from narcissistic disorder, such as big ego, over-self confidence, exploitation of Interpersonal relationships, arrogance, and deficient social conscience. The triggers were rationalization and projection.